Etiology and Management of Blunt Liver Trauma in a Tertiary Care Hospital (Medical Forum Monthly, 2024)
Objective: The increasing prevalence of bullet injuries and road traffic accidents poses significant challenges for the improvement in trauma management especially blunt liver trauma due to its location and being a high vascular organ. The present study aimed to determine the etiology and management of blunt liver trauma.Study Design: A cross-sectional studyPlace and Duration of Study: This study was conducted at the Department of General Surgery, Saidu Group of Teaching Hospitals Saidu Sharif Swat, (SGTH) from February 2022 to September 2022.Methods: Patients presented with various injuries were examined and detail history was taken regarding the types of injuries and comorbid status. Head to toe examination was done. HBsAg and HCV and HIV status, Urea, creatinine and Random Blood Sugar Level (RBS), X-ray erect abdomen/ lateral decubitus position, Ultrasound abdomen, Peritoneal aspiration, and CT scan were performed on each patients. SPSS version 27 was used for data analysis.Results: The overall mean age was 40.82±6.82 years. Age-wise distribution of patients were as follows: 136 (54.2%) in 10-25 years, 60 (25.4%) in 26-40 years, and 40 (16.9%) in 41-55 years. There were 144 (61%) males and 92 (39%) females. Road traffic accident (RTA) was the most prevalent mechanism of injury found in 98 (41.5%) cases, followed by fall from height 76 (32.2%), physical assault 38 (16.1%), and Sport’s injury 24 (10.2%) cases. The incidence of successful conservation management was 77.1% (n=182). The mortality rate was 36.4% (n=86).Conclusion: The present study observed that the severity of blunt liver trauma had significant association with probability of successful conservative management. Limited hospital resources and a lack of consensus on traditional treatment methods adversely affected success.